A Synergistic Model of Technological Capacity, Institutions, and Culture in the Transition Towards Society 5.0: Cross-Country Evidence - Ruslan Puzikov; Vadim Ponkratov; Victor Renobell; Nurlan Kaldibayev; Marina Vasiljeva; Maria Volkova; Larisa Ovcharenko; Dostonbek Eshpulatov; Elena Kireeva; Olesya Dudnik (Emerging Science Journal, 2026)
This study elucidates global variation in achieving Society 5.0 objectives by identifying the foundational requirements, thresholds, and synergistic configurations of technological and AI capacity, institutional quality, and cultural values across nations. The research develops a novel conceptual model that integrates core determinants while accounting for country-specific conditions in the transition towards a human-centered society. Utilizing a harmonized dataset encompassing 102 countries, this study employs hierarchical multiple regression and three-way interaction modeling to evaluate the direct, conditional, and higher-order effects of technological readiness and its interaction with institutional and cultural values on Human-Centered Outcomes (HCO). The empirical results demonstrate that technological advancement and AI readiness alone are insufficient to generate meaningful societal progress. Instead, institutional quality emerges as the most robust predictor, significantly amplifying the relationship between digital capacity and human-centered outcomes. Among cultural dimensions, power distance exhibits the most pronounced constraining effect, while individualism and long-term orientation display consistent but statistically weaker patterns. These findings elucidate the paradox of divergent national outcomes arising from AI integration, leading to a new country taxonomy based on empirical proximity to the Society 5.0 benchmark. Ultimately, the article challenges technocentric narratives and advances a co-evolving concept of socially embedded change, providing actionable insights into how technological, institutional, and cultural pillars must be aligned to foster inclusive and well-being-oriented digital transformation.